The impact of tax uncertainty on irreversible investment - Rainer Niemann (Center for Economic Studies and ifo Institute (CESifo), 2007)
Tax legislation, fiscal authorities, and tax courts create tax uncertainty by frequent tax reforms and various different interpretations of the tax law. Moreover, investors generate model-specific tax uncertainty by using simplified models that anticipate the actual tax base incorrectly. I analyze the effects of stochastic taxation on investment behavior in a real options model. The investor holds an option to invest in an irreversible project with stochastic cash flows. To cover the effects of both tax base and tax rate uncertainty, the investment's tax payment is modelled as a stochastic process. Increased tax uncertainty has an ambiguous impact on investment timing. The view that tax uncertainty depresses real investment is rejected. A higher expected tax payment delays investment. A higher tax rate on interest income affects investment timing ambiguously.
Keywords: H25; G31; 330; Betriebliche Investitionspolitik; Investition; Realoption; Irreversibility of Investment; Steuer; Risiko; Theorie